2/3(6x - 9) = 0 (your statement)

4x - 6 = 0 (apply distributive rule)

4x - 6 + 6 = 0 + 6 (add 6)

4x = 6 (collect terms)

4x/4 = 6/4 (divide by 4)

x = 6/4 (simplify)

x = 3/2 (simplify fraction)

x = 1 1/2 (convert into improper fraction)

Alternate forms for 2/3(6x - 9):

4x - 6 (apply distributive rule)

2(2x - 3) (factor)

4x - 6 = 0 (apply distributive rule)

4x - 6 + 6 = 0 + 6 (add 6)

4x = 6 (collect terms)

4x/4 = 6/4 (divide by 4)

x = 6/4 (simplify)

x = 3/2 (simplify fraction)

x = 1 1/2 (convert into improper fraction)

Alternate forms for 2/3(6x - 9):

4x - 6 (apply distributive rule)

2(2x - 3) (factor)